Pengaruh Relaksasi Benson Terhadap Nyeri Pada Pasien Post Operasi Benigna Prostat Hyperplasia Di RSUD MGR. Gabriel Manek Atambua - Yerry Soumokil; Yuyun Septiani Sukadi; Sherly Pattipeilohy (Journal of Educational Innovation and Public Health, 2023)
Benign Prostatic Hyperplasia (BPH) is an enlargement of the prostate that can cause obstruction of the prostatic urethra. One of the measures to treat patients with benign prostate hyperplasia is surgery. Surgery can irritate the bladder mucosa, causing pain. One of the non-pharmacological pain management that can be used is Benson relaxation. This relaxation is an action to free mentally and physically from tension and stress so that it can increase tolerance to pain. The purpose, the application of Benson relaxation was carried out for 2 days with a frequency of 2 times a day and a duration of 15 minutes. Methods of this research includes descriptive research with a case study approach, which aims to determine the description and effect of differences between 1 patients in the application of Benson therapy to reduce pain in postoperative patients with benign prostatic hyperplasia. The results of study, researchers get an overview of the application of benzene therapy so that the results show that both respondents experienced a decrease in pain, the respondent complained of pain on a 6 scale after 2 days of benzene relaxation pain complaints decreased with a pain scale of 3. In conclusion, the application of Benson relaxation has an effect on reducing pain scale in postoperative patients with benign prostate hyperplasia.